2017
DOI: 10.1007/s13346-017-0397-0
|View full text |Cite
|
Sign up to set email alerts
|

User input in iterative design for prevention product development: leveraging interdisciplinary methods to optimize effectiveness

Abstract: The development of HIV-preventive topical vaginal microbicides has been challenged by a lack of sufficient adherence in later stage clinical trials to confidently evaluate effectiveness. This dilemma has highlighted the need to integrate translational research earlier in the drug development process, essentially applying behavioral science to facilitate the advances of basic science with respect to the uptake and use of biomedical prevention technologies. In the last several years, there has been an increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…A 2017 landscape mapping of end-user research in HIV prevention for young women in sub-Saharan Africa identified 53 projects, of which 3 were explicitly HCD. 41 There is often overlap in objectives and methods between HCD, more traditional qualitative methodologies 42,43 ; participatory research 11 ; engineering approaches 44,45 ; and discrete choice experiments as formative research. 46 Although efforts have been made to compare and contrast approaches, 8 distinctions are not concrete.…”
Section: Discussionmentioning
confidence: 99%
“…A 2017 landscape mapping of end-user research in HIV prevention for young women in sub-Saharan Africa identified 53 projects, of which 3 were explicitly HCD. 41 There is often overlap in objectives and methods between HCD, more traditional qualitative methodologies 42,43 ; participatory research 11 ; engineering approaches 44,45 ; and discrete choice experiments as formative research. 46 Although efforts have been made to compare and contrast approaches, 8 distinctions are not concrete.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple acceptability surveys of preferred vaginal formulations have found support for odorless and colorless gel products and can be an important guide to the development of new vaginal gel products [ 84 ]. Recent studies have provided important information regarding user preferences for the physical and aesthetic properties of gel formulations and can be used to guide MPT formulation composition [ 85 , 86 ].…”
Section: Multipurpose Prevention Technologiesmentioning
confidence: 99%
“…As development of intravaginal systems for delivery of preventive agents continues, the importance of understanding the user experience as part of the preclinical design process is being acknowledged. [ 26 , 27 ] Our results provide evidence to support continued development of this platform, and offer a considered look at issues that will likely impact the development of vaginal products for long-term use in prevention of HIV, as well as new contraceptive methods and MPTs.…”
Section: Discussionmentioning
confidence: 64%